The Bureau of Agricultural Research the research and outreach subproject - a terminal report - Bonifacio, Manuel Flores ([s.l. s.n., 1991)
It was stated in the UNCRD proposal that "This study should particularly shed light on social development policy objects as well as on the role of the local community as one of the actors in social development. The scope and approach of social development and the range of the local community's role depend on the structure of each country's social system. Hence to identify measures for develop of people's livelihood and welfare, economic activities, and resource management, it is necessary to development a conceptual framework. Such a framework would help provide a theoretical understanding of social developemnt in the ideal sense and the actual role of the local community within the context of its existing social system." (Underscoring supplied). Thispaper wii then provide a conceptual sketch needed in order to understand the community int he context of social development. Current thinking in the field of rural development has given stronger emphasis on the role of people in the process of development. It appears that previous approaches have unfortunately neglected the central role of the social factors in the process. Yet, while there is a general agreement on the role of the social factors in the development, experts are still in search of a more adequate conceptualization of such factors. It is hoped that thesucceeding discussion will help contribute toward a better understanding of the role of the social factors in local development. The UNCRD is quite correct in delineating the issue of local development within the context of a community. It is to be rcognized that there has been much debate on the concept community. In whatever way it is defined, what should be immediately recognized is that it should be taken in the general context of human relationship. For our purpose, a community is defined as a group of people living in a specific geographical space where they have assumed residence. The idea of residence is central to the definition of a community because stable relationship with others through time will become possible. Such stable relationship is vital since, to be a legitimate member of the community, one must embrace its values and norms and make them part of his day-to-day activities. Hence to be a resident of a community immediately assumes that one is embracing its norms and contributing to the maintenance of its normative order.
Research Paper.